Different paths? Human capital prices, wages and inequality in Canada and the US - Audra J. Bowlus; Chris Robinson (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
In the last three decades, Canada and the US showed different paths in per capita GDP growth, skill premiums and inequality. Both firm and worker productivity differences play a role and have different policy implications, but are difficult to distinguish. To examine separate firm and worker productivity effects, human capital prices and quantities are estimated using the methods developed in Bowlus and Robinson (2012). The quantities reflect worker productivity while the prices tend to reflect firm productivity. In the US there was faster growth and a much more rapid rise in skill premia and inequality. This was primarily due to different paths for the relative price paid to rent high skilled human capital in the two countries, rather than differences in relative quantities of human capital supplied by the typical high skilled worker. Worker productivity increased for high skilled workers, but decreased for low skilled workers over the 1980-2000 period.
Keywords: 330